Perceived Forest-based Ecosystem Services and Attitudes Toward Forest Rehabilitation: A Case Study in the Upstream of Central Java, Indonesia - Prasetyo Nugroho; Shinya Numata; Nur Abdi Aprilianto (Jurnal Ilmu Kehutanan, 2020)
Forest rehabilitation is essential in restoring forest-based ecosystemservices (ES) provided by forest area. However, the critical issue on how locals perceived importance of forest rehabilitation, and how forest rehabilitation generates, both direct and indirect, benefits for the adjacent communities has remained contentious. A questionnaire survey was employed to examine locals' perceived importance, perceived ES, and attitudes toward forest rehabilitation in a village adjacent to Perhutani's forest area in the upstream of a catchment in Central Java, Indonesia. In total, 90 usable questionnaires were collected. The findings indicate that their perceived pine-sap production, conserving forest area, and water availability are the importance of forest rehabilitation programs. Locals recognized various ES benefits, including provisioning, regulating, supporting, and cultural services, though the adverse impacts emerged. Spearman rank correlation analysis revealed that local's satisfaction with forest rehabilitation positively and significantly correlated with their positive perceptions and subsequently increase their willingness to be actively involved in forest conservation efforts. The findings also imply that forest managers should not only focus on delivering benefits but also be aware of the adverse impacts of forest rehabilitation and management practices, which are crucial for ensuring forest sustainability. Jasa Ekosistem Berbasis Hutan yang Diterima dan Sikap terhadap Rehabilitasi Hutan: Studi Kasus di Hulu Daerah Aliran Sungai di Jawa Tengah, IndonesiaIntisariRehabilitasi hutan penting untuk memulihkan jasa ekosistem berbasis hutan yang disediakan oleh kawasan hutan. Sementara rehabilitasi hutan sangat penting dalam memulihkan jasa lingkungan, pertanyaan mengenai bagaimana penduduk setempat memandang pentingnya rehabilitasi hutan, dan bagaimana rehabilitasi hutan menghasilkan manfaat, baik langsung maupun tidak langsung, bagi masyarakat sekitar masih diperdebatkan. Kuesioner survey dilaksanakan untuk menggali persepsi masyarakat tentang tingkat kepentingan, persepsi terhadap jasa lingkungan, dan sikap mereka terhadap rehabilitasi hutan di desa berdekatan kawasan hutan Perhutani, di hulu daerah alisan sungai, Jawa Tengah, Indonesia. Secara total, 90 kuesioner yang lengkap berhasil dikumpulkan. Temuan menunjukkan bahwa persepsi masyarakat terhadap pentingnya rehabilitasi hutan yaitu untuk produksi getah pinus, melestarikan kawasan hutan, dan ketersediaan air. Masyarakat desa merasakan berbagai jasa lingkungan yang diperoleh dari kawasan hutan meliputi manfaat penyediaan, pengaturan, dukungan, budaya, meskipun dampak negatif juga teramati. Analisis korelasi Spearman menunjukkan bahwa kepuasan masyarakat terhadap rehabilitasi hutan berkorelasi positif dan signifikan terhadap persepsi positif mereka, dan selanjutnya akan meningkatkan kesediaan mereka untuk terlibat aktif dalam upaya konservasi kawasan hutan. Temuan ini juga menyiratkan bahwa pengelola hutan tidak hanya fokus memberikan manfaat, tetapi harus juga menyadari dampak buruk dari praktik rehabilitasi dan pengelolaan hutan yang muncul untuk memastikan kelestarian hutan.